2021
DOI: 10.1002/ird.2657
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimum applied water and seeding rates for winter wheat by using AquaCrop and mathematical‐economic analysis*

Abstract: The growing scarcity of water resources has made the need to optimize water consumption in the agricultural sector inevitable. In this study, the accuracy of the AquaCrop model in simulating the yield and dry matter of winter wheat under different plant densities and water levels was evaluated. Then using economic-mathematical analysis, the optimum values of plant density and irrigation water were determined. Next, using time-series models, the values of optimum irrigation water and economic yield were forecas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For 2016-2018 absolutely dry weight of 100 plants of winter wheat exceeded the weight of plants from crops after spring barley by 53-55% when sowing on September 5 and by 39-40% when sowing 15 October [19]. The difference was: with early sowing (September 5) 33-40%, with late sowing (October 15) 17-27% [20].…”
Section: Resultsmentioning
confidence: 94%
“…For 2016-2018 absolutely dry weight of 100 plants of winter wheat exceeded the weight of plants from crops after spring barley by 53-55% when sowing on September 5 and by 39-40% when sowing 15 October [19]. The difference was: with early sowing (September 5) 33-40%, with late sowing (October 15) 17-27% [20].…”
Section: Resultsmentioning
confidence: 94%
“…In cultivation practice, reasonable population structure can alleviate the contradiction between population and individual, coordinate the relationship among yield components, improve the canopy structure to ensure the full use of light energy, and ultimately achieve high yield [4]. Previous studies indicated that a reasonable high-yield population structure could be constructed by adjusting the basic seedling density, nitrogen fertilizer management, or a combination of the two [5,6].…”
Section: Introductionmentioning
confidence: 99%